Keefektifan Penggunaan Teknik Permainan Kartu Huruf Lontarak Dalam Pembelajaran Kosakata Bahasa Makassar Siswa Sekolah Dasar - Nurkardiyanti Nurkardiyanti; Johar Amir; Nurhusna Nurhusna (HUMAN: South Asian Journal of Social Studies, 2023)
Abstract. This study aims to prove the effectiveness of using the lontarak card game technique in learning Makassar language vocabulary for fourth grade students of SD No.191 Inpres Paku Kab.Takalar. This type of research is pre-Experimental in the form of One Group Pretest-Posttest research. The population in this study were all students of class IV SD No.191 Inpres Paku Kab.Takalar totaling 25 people. The sample in this study consisted of all the population of class IV SD No.191 Inpres Paku Kabupaten Takalar, totaling 25 people. The sampling technique in this study used saturated sampling. The technique used to collect data in this study is using a written test. The research procedures included planning, pretest, treatment, posttest, and the results of the pretest and posttest were compared with the appropriate statistical tests. The results of Makassar language vocabulary learning in the pretest have an average score of 56.9 and can be categorized as low, and the results of Makassar language vocabulary learning in the posttest have an average score of 90.5 and are categorized as high. Comparison of the average Makassar language vocabulary learning score before and after treatment increased by 33.6. The results showed that, t_count = 62.25 and t_table = 2.064, then t_count ≥ t_table or 62.25 ≥ 2.064 was obtained. So that it can be said that H_0 is rejected and H_1 is accepted, this means that there is an influence of using the ejection card game technique on learning Makassar language vocabulary in class IV SD No.191 Inpres Paku Kabupaten Takalar. Keywords. Techniques of Lontarak Letter Card Game, Vocabulary Learning